2023
DOI: 10.1111/jvh.13811
|View full text |Cite
|
Sign up to set email alerts
|

Bulevirtide‐based treatment strategies for chronic hepatitis delta: A review

Abstract: Chronic hepatitis Delta (CHD) is a rare and severe form of chronic viral hepatitis.Until recently, the only therapeutic approach has been the off-label use of a 48 weeks course of PegInterferon alpha (PegIFNα), that was characterized by suboptimal efficacy and burdened by significant side effects that limited treatment applicability in patients with advanced liver disease. In July 2020, European Medicines Agency (EMA) conditionally approved the entry inhibitor Bulevirtde (BLV) at the dose of 2 mg/day for the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…The closest to approval in the USA is bulevirtide, a first-in-class entry inhibitor that targets a polypeptide hepatocyte receptor for HBV and HDV. After its conditional approval in the European Union, multinational studies have shown that it is well-tolerated and have high rates of virological response both alone and in combination with PEG-INFα therapy 15 . A large phase 3 trial examining ritonavir-boosted lonafarnib with or without PEG-IFNα has been completed that showed significant virologic response at 24 weeks and a well-tolerated treatment regimen compared to placebo 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The closest to approval in the USA is bulevirtide, a first-in-class entry inhibitor that targets a polypeptide hepatocyte receptor for HBV and HDV. After its conditional approval in the European Union, multinational studies have shown that it is well-tolerated and have high rates of virological response both alone and in combination with PEG-INFα therapy 15 . A large phase 3 trial examining ritonavir-boosted lonafarnib with or without PEG-IFNα has been completed that showed significant virologic response at 24 weeks and a well-tolerated treatment regimen compared to placebo 16 .…”
Section: Discussionmentioning
confidence: 99%
“…After its conditional approval in the European Union, multinational studies have shown that it is well-tolerated and have high rates of virological response both alone and in combination with PEG-INFα therapy. [15] A large phase 3 trial examining ritonavir-boosted lonafarnib with or without PEG-IFNα has been completed that showed significant virologic response at 24 weeks and a welltolerated treatment regimen compared to placebo. [16] A phase II trial of REP 2139, a nuclear acid polymer that inhibits the release of HBsAg, also showed promising results after 1 year of treatment.…”
Section: Cancer Screening In Chronic Hepatitis D Infectionmentioning
confidence: 99%
“…As an extension of the numerous viral targets and DAAs taken into account for antiherpesviral drugs so far, the inclusion of host targets into the therapy strategy presents an advanced approach with the potential of resolving problems arising from viral resistance formation. So far, only a few examples of target-specific antiviral HDAs have been established in clinical treatment regimens, such as maraviroc [ 62 ], ribavirin [ 63 ] and bulevirtide [ 64 , 65 ], for the antiviral therapy of infections with HIV and hepatitis viruses B or D, respectively. Our concept of CDKs as novel anti-HCMV targets might broaden this current repertoire of antivirals and might include the option of HDA + DAA combination treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from clinical trials with viral response and improvements in hepatic inflammation as well as favorable safety profile have been reproduced in real-world cohorts. [11,15] However, data on the optimal treatment duration and long-term clinical endpoints, such as the prevention of hepatic decompensation or HCC are still lacking. Pausing or terminating BLV might be possible in selected patients [16] while reliable biomarkers for safe treatment termination remain elusive.…”
Section: No Hepatic Comorbiditiesmentioning
confidence: 99%